A Feminist viewpoint on the subjectx of social transformation in Our America - Fabbri, Luciano (Pontifícia Universidade Católica de São Paulo, 2011)
This article is part of a series of efforts aiming to systematize and deepen some further thoughts on the challenges of social and popular movements in the current context, recovering some expressions of contemporary Feminisms that, in an antisexist, anti-racist and anti-capitalist perspective, contribute to the strategy and the challenge of thinking the subjectx of social transformation.